Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Seated: Louise Erickson and Marcia McLane; Standing: Lindell Cross talking with Mary Ellen Clay in background